2014
DOI: 10.1128/jvi.01935-14
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Virus Inhibits Type I Interferon Induction by ORF1 Products

Abstract: Hepatitis E virus (HEV) causes both endemic and epidemic human hepatitis by fecal-oral transmission in many parts of the world. Zoonotic transmission of HEV from animals to humans has been reported. Due to the lack of an efficient cell culture system, the molecular mechanisms of HEV infection remain largely unknown. In this study, we found that HEV replication in hepatoma cells inhibited poly (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
144
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(154 citation statements)
references
References 54 publications
10
144
0
Order By: Relevance
“…As different studies have reported that HEV is able to counteract the IFN‐stimulated gene (ISG) response in human liver cells,34, 35 we next investigated the viral restriction of the IFN pathway by determination of ISG expression after HEV transfection in placental‐derived cells. JEG‐3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As different studies have reported that HEV is able to counteract the IFN‐stimulated gene (ISG) response in human liver cells,34, 35 we next investigated the viral restriction of the IFN pathway by determination of ISG expression after HEV transfection in placental‐derived cells. JEG‐3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To date, the role of viral macro domains has been demonstrated in the modification of cellular response to viral infection (Nan et al, 2014;Nargi-Aizenman et al, 2002;Tan et al, 2009), as a possible RNA recruitment factor (Malet et al, 2009), or in minus-strand synthesis, P23 processing and/or viral replication (LaStarza et al, 1994a(LaStarza et al, , 1994bLulla et al, 2011). The molecular mechanism or biochemical function behind this role is not well understood.…”
Section: Proteinmentioning
confidence: 97%
“…2). As antagonists of IFN type I induction, two domains in the HEV ORF1, X and papain-like cysteine protease domain (PCP), were identified by Nan et al (32). Interestingly, in vivo studies with HEV-and HCVinfected chimpanzees were also conducted to compare the innate immune responses of these two viruses.…”
Section: Discussionmentioning
confidence: 99%